Development of a Novel Cytochrome b Real-Time PCR Assay for Identification of Plasmodium malariae - Dinh Thi Thu Hang; Vu Thi Nga; Hoang Van Tong; Hoang Xuan Su; Le Quoc Tuan; Nguyen Van Chuyen; Nguyen Thi Minh Trinh; Ho Anh Son (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
This article aims to establish a novel cytochrome b real-time PCR assay using Taqman probe for identification of P. malariae and its discrimination from other Plasmodium human infecting species. The optimization of real-time PCR assay with 1X QuantiTect Probe PCR Master Mix, primers and probe used at concentrations of 0.4 μM and 0.1 μM, respectively; and 2.5 mM MgCl2, 5 μl DNA template and deionized H2O of 20 μl, was performed using a real-time PCR instrument. The developed real-time PCR assay was evaluated for the limit of detection, stability on standard panels (109-100 copies/ µl), as well as the sensitivity, specificity on control groups. The probit analysis demonstrates that the 95% detection limit was